Kajian Paket Teknologi Budidaya Bawang Merah Dataran Tinggi Musim Kemarau di Kabupaten Rejang Lebong - Yahumri; Shannora Yuliasari; Miswarti Miswarti; Wilda Mikasari; Taufik Hidayat; Darkam Musaddad (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2022)
Production of onion shows a negative development towards demand for onion. Several technological innovations to support development of onion are needed in an effort to increase production and productivity. Cultivation technology innovation is not sufficient technological needs of various ecosystem locations. Existing research results have not been fully utilized. This study aims to examine technology package for upland onion cultivation in dry season in Rejang Lebong Regency. Study was carried out using an On Farm Research (OFAR) approach involving 4 cooperative farmers on an area of ​​2,400 m2. Technology applied to introduction technology package and improved technology package which is compared to farmer technology. Results of study showed that application of introduction technology package, use of onion seeds of Batu Ijo variety with fertilization technology using a combination of chicken manure and cow manure with a percentage ratio (75:25) of 20 tons/ha, SP-36 fertilizer 250 kg/ha, fertilizer Urea 250 kg/ha, ZA fertilizer 500 kg/ha and KCl 250 kg/ha and a spacing of 15 x 20 cm were able to produce shallot bulbs with a productivity of 24.28 tons of wet weight/ha.